GLOVE PUPPET AND ITS DISTINCTIVE FEATURES (Modern American Journal of Linguistics, Education, and Pedagogy, 2025)
Glove puppets are among the most popular and widely used types in puppet theater. With their long history and diverse applications, they remain an essential tool for puppeteers. This article provides information about glove puppets and their unique characteristics.